PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA AVANZA PADA PT ASTRA INTERNATIONAL TBK; AUTO 2000 MEDAN CABANG - Wijaya, Hendra; Samvara, Made Adhiguna; Hutagaol, Jarunjung; Butar-Butar, Mangasi; Calvin, Calvin; Rudiyanto, Rudiyanto (EDUTECH CONSULTANT, 2019)
The research objective is to test and analyze the effect of service quality and promotion on purchasing decisions of Toyota Avanza cars at PT Astra International Tbk; Auto 2000 Medan Krakatau Branch. The approach of this research is quantitative research. The results of the study which conclude is that service quality partially has a significant effect on the decision to purchase a Toyota Avanza car at the Auto 2000 Medan Krakatau Branch. Partial promotion has a significant effect on the decision to purchase a Toyota Avanza car at the Auto 2000 Medan Krakatau Branch. Service Quality and promotion simultaneously have a significant effect on purchasing decisions of Toyota Avanza cars in Auto 2000 Medan Krakatau Branch with adjusted R Square of 61.3% and the remaining 38.7% are varied by other factors not examined such as price, product and quality product.